As aberturas do complexo: uma análise da religiosidade no pensamento de Edgar Morin - Stigar, Robson (2018)
The work of Edgar Morin is developed on the aegis of complexity, seeking in this way to analyze reality through the various areas of knowledge. In view of this characteristic of complex thinking, it may be posited that no area of knowledge should or can be excluded from its analysis. In this sense, religiosity, although not directly addressed in the author's writings, can and should be considered as an object of investigation. In this perspective, the general objective of this study is: to analyze the way in which the religiosity in the thought of Edgar Morin is found. The investigative itinerary was guided by the following problematic: what are the assumptions of Morin's work that allow access to religiosity? For that, the biographical and philosophical route from which Morin structures his epistemological assumptions was analyzed. In this were access routes - mythical, ethical and scientific - that allow the contextualization of the theme of religiosity in the thought of the author. Thus, it is argued in this thesis that Edgar Morin's thought has a religious perspective, which is accessed through three foundations of the method by which it constitutes the epistemology of complexity: myth, ethics and science. This study does not exhaust the possibilities of research on the question of religiosity in Morin's thought. But, it is intended to enable a critical reflection on religiosity and its new configurations, in the context of contemporaneity